Thriving in chaos: do more with these 10 tools in teaching and research / Dr. Aisyah Saad Abdul Rahim - Abdul Rahim, Aisyah Saad (Faculty of Pharmacy, 2023)
The COVID-19 pandemic has propelled many of us into establishing presences in the physical and digital worlds. Now returning to the normal routines in the post-pandemic era, technology is closely intertwined with our daily lives. Not only the online presence in social media but across the different sectors - banking, retail, health and education.